The principal's guide to a powerful library media program - McGhee, Marla W. (Gale virtual reference library, 2005)
A handbook that describes a specific collaborative process for library media specialist and classroom teacher to use in planning teaching units. Written for K-12 educators. Also provides suggested book lists, web sites, and professional resources.